Perspectives of electric supply of municipal housing consumers in cities of Uzbekistan - A.G.Saidkhodjaev,Yu Bobojonov, U M Turdiev (International Journal of Advanced Science and Technology, 2020)
The article discusses the main prospects for the development of electricity supply for householdconsumers in the cities of the Republic of Uzbekistan. To solve the increased requirements for thereliability of power supply, it is proposed to use complex-connected electric networks, the introduction ofautomation and digital energy, an automatic system of commercial energy metering (ASCEM), as well asthe use of reactive power compensation in urban electric networks.